Knowledge management system in health and social care: review on 20 practiced knowledge management systems - Ridhwan, Muhammad Saiful; Oyefolahan, Ishaq Oyebisi (School of Business and Management, Institut Teknologi Bandung, 2013)
The importance of managing medical information has become very critical in the healthcare delivery system. Medical information nowadays are optimized towards serving different areas such as; diagnosing of diseases, planning and administration, treatment and monitoring of patient outcomes, services and costs. This article provides a review into various Health and Social Care systems which encompasses the Knowledge Management value. For analysis, more than 30 systems that are related to Health and Social Care were gathered via Internet research, only 20 of these systems were finally selected based on recent system development and popularity of the system.